The influence of agricultural treatment type on the microbial properties of sod-podzolic soil - A. D. Zhelezova; D. I. Passova; D. A. Nikitin; M. A. Yashin; S. V. Zhelezova (Бюллетень Почвенного института им. В.В. Докучаева, 2019)
In this study we examined the effects of conventional agricultural treatment with plowing and no-till treatment on the physical, chemical and microbiological properties of agro-transformed sod-podzolic loamy soil. Soil was sampled in eightfold spatial replication from the arable layers (0–10, 10– 20, 20–30 cm) of field No. 2 of the long-term field experiment of the Center for Precision Agriculture of the Russian State Agrarian University in June, 2018. The crop type on the field No. 2 was vetch and oat mix. Moisture content, water holding capacity, pH, percentage of carbon and nitrogen were determined. The NDVI vegetation index was measured using GreenSeeker HandHeld and used to estimate the plant development intensity. Microbiological properties were assessed by selective plate counts. The abundance and activity were estimated for the next ecological and trophic groups of microorganisms: heterotrophic ammonifiers, aerobic and anaerobic nitrogen-fixing agents, denitrifiers, oligotrophs, cellulolytics. The vegetation index NDVI was higher for plants growing on the plowed part of the field. The differences in microbiological properties when comparing soil samples under no-till and under plowing were insignificant (by t-test for the independent groups comparison). In no-till samples a greater number of micromycetes, including cellulolytic and phytopathogenic, was observed compared to conventional treatment. Profile distributions of bacterial and fungal gene abundances were similar for both treatments according to the paired comparison of samples from different layers. The similarity in microbiological properties was found in the condition of a higher moisture content of the arable layer of the soil and a higher percentage of nitrogen were revealed in the soil under no-till compared with the soil treated by plowing.